2023
DOI: 10.1111/bph.16167
|View full text |Cite
|
Sign up to set email alerts
|

The role of gut microbiota in cerebrovascular disease and related dementia

Abstract: In recent years, increasing evidence suggests that commensal microbiota may play an important role not only in health but also in disease including cerebrovascular disease. Gut microbes impact physiology, at least in part, by metabolizing dietary factors and host‐derived substrates and then generating active compounds including toxins. The purpose of this current review is to highlight the complex interplay between microbiota, their metabolites. and essential functions for human health, ranging from regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 157 publications
0
2
0
Order By: Relevance
“…As metagenomics research progresses, our comprehension of the gut microbiota has grown, elucidating their increasingly evident connection with various diseases. For instance, gut microbes influence physiology by partially breaking down dietary components and substances produced by the host, leading to the production of bioactive compounds, including toxins ( 47 ). Gut microorganisms have a central role in regulating the overall purine balance and serum uric acid (UA) levels in the host ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…As metagenomics research progresses, our comprehension of the gut microbiota has grown, elucidating their increasingly evident connection with various diseases. For instance, gut microbes influence physiology by partially breaking down dietary components and substances produced by the host, leading to the production of bioactive compounds, including toxins ( 47 ). Gut microorganisms have a central role in regulating the overall purine balance and serum uric acid (UA) levels in the host ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have found differences in GM composition between healthy people and people with cognitive impairment or different types of cognitive impairment, attempting to use this information to make a diagnosis of the disease ( Guo et al, 2021 ; Hung et al, 2022 ). Therefore, clarifying the influence of different flora on dementia is essential for ascertaining new therapeutic targets for dementia and diagnosing dementia using microbial profiles ( Liu et al, 2019 ; Guo et al, 2021 ; Cuartero et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In part by interacting with the immune system, increasing evidence suggests that commensal microbiota have a major role both in homeostasis and in pathological contexts including cerebrovascular diseases. In this vein, Cuartero et al (2024) underscore the intricate interplay between microbiota and metabolism, immunity, brain development and function. Specifically, the possible participation of microbiota-derived products in post-stroke cognitive impairment and dementia is discussed, including potential therapeutic opportunities ranging from probiotics and prebiotics, antibiotics, and faecal microbiota transplantation.…”
mentioning
confidence: 99%